IMPLEMENTATION OF CUSTOMARY FOREST MANAGEMENT POLICY IN SUPPORTING THE SUSTAINABILITY OF PROGRESSIVE NATIONAL DEVELOPMENT GOALS IN PROVINCE ACEH - Faez Syahroni; Riswan Z; Zulkri; Abdul Manan; Saprijal; Agus Junaidi (RADJA PUBLIKA, 2025)
Customary forests in Aceh Province play a crucial role in preserving the environment while strengthening the socio-cultural identity of the mukim community. Since Constitutional Court Decision No. 35/PUU-X/2012, customary forests have been legally recognized, but their implementation still faces challenges such as weak coordination, limited funding, and minimal oversight. This study aims to analyze the implementation of customary forest policies in Aceh, focusing on supporting and inhibiting factors, and to formulate policy strategies aligned with the sustainable development goals (SDGs), specifically Goal 13 (climate action) and Goal 15 (terrestrial ecosystems). The method used is descriptive qualitative research through in-depth interviews, field observations, and documentation, with informants from local governments, customary institutions, NGOs, and mukim communities. Data analysis was conducted using the Miles and Huberman approach, which includes reduction, presentation, and conclusion drawing. Initial results indicate a gap between formal regulations and implementation practices, where local regulations such as the Qanun on Customary Mukim Forests are more effective in supporting implementation than general national policies. This research is expected to produce applicable policy recommendations to strengthen coordination, resources, and participation of indigenous communities in forest management.